Forensic systems engineering : evaluating operations by discovery - Stimson, William A. (Wiley series in systems engineering and management, 2018)
"Forensic Systems Analysis addresses relatively new developments in two professions: the law and engineering. The author covers the theory of process liability, management of operations, process liability and operations, analysis of dysfunctional processes, process risk analysis, and process/product verification and validation. He also discusses process stability, capability, and reliability. The narrative is addressed to both plaintiff and defendant and offers analyses that present novel uses of traditional engineering methods concerning risk and product quality and reliability. The presented methodologies and arguments are equally valid when applied to service industries. Managers, engineers, technicians, auditors, and diverse analysts benefit from the book's rigorous approach to system tactics and constraints related to product and service operations"--